Analysis of wireless sensor network lifetime / Mohd Ismail Abdan - Abdan, Mohd Ismail (2012)
Sensor technologies are common in the past for collecting information about specific environment but nowadays wireless sensor network are getting popular and widespread used in every sector. A wireless sensor network is characterized by number of sensor nodes distributed in the field to monitor certain environment parameter. Usually these tiny sensor nodes are powered by small battery. Due to the limited energy capacity, power efficiency is a big challenge to maintain the availability of the network. Some of the network characteristic and behavior has a direct impact on the network lifetime. Configuring the optimal parameters is vital for sensor nodes to handle energy resource efficiently. This research studies the parameters that most significantly impact the energy consumption and find their correlation and trade offs with respect to network lifetime. In this research the trade offs were investigated in detail in various combinations. To fulfill this objective a discrete simulation tool OMNeT++ (with MiXiM framework) has been chosen to model and simulate the real environment of the sensor nodes. Using this tool the correlation of the selected parameters with regards to network lifetime has been analyzed. Finally, results of extensive simulation are presented and hopefully can become guidance for the sensor network designers to optimally configuring the correct parameters for prolonged network lifetime.